Peran Badan Usaha Milik Desa Dalam Meningkatkan Perekonomian Masyarakat Desa Sekapuk Kecamatan Ujungpangkah Kabupaten Gresik - Agnes Yuniar Pradita; Deasy Arieffiani; M. Husni Tamrin (Policy and Maritime Review, 2023)
The purpose of this study was to determine the role of BUM Desa in improving the economy of rural communities and to determine the supporting and inhibiting factors for the role of BUM Desa in improving the economy of the people of Sekapuk Village, Ujungpangkah District, Gresik Regency. The type of research used in this study is descriptive qualitative. Data collection techniques in this study were carried out by interviews, observation, and documentation. The research results obtained from this study indicate that the Role of Village-Owned Enterprises (BUM Desa) Iso Wiguno in Improving the Economy of Village Communities in Sekapuk Village has played a good role, but there are sub-indicators that have not met community expectations, namely in the aspects of coaching and loan funds, because the community hopes to get other guidance and bigger capital from BUM Desa Iso Wiguno. The supporting factors in this study are that Sekapuk Village has adequate natural and human resources, and has many programs with an easy flow. The inhibiting factors in this study were the type of training and capital. BUM Desa Iso Wiguno Sekapuk Village needs to hold training related to proper business management procedures, BUM Desa Iso Wiguno Sekapuk Village seeks to establish cooperation with other parties related to capital so that people can develop their business without worrying about their initial capital to start a business, BUM parties Iso Wiguno Village needs comparative study activities with other BUM Desa, especially BUM Desa Iso Wiguno in order to be able to carry out program innovations.